Beyond digital narratives: How ethical concerns shape Gen Z’s ESG investment choices - Astama, I Ketut; Darma, Gede Sri (International research journal of management, IT and social sciences, 2025)
This study aimed to analyze the factors influencing Generation Z’s sustainable financial investment intention in Indonesia, focusing on the roles of digital banking, social media, and ethics, along with the moderation of Artificial Intelligence (AI) and financial literacy. Motivated by the paradox between high ESG awareness and low actual investment participation, the study utilized an integration of the Theory of Planned Behavior and the Unified Theory of Acceptance and Use of Technology applying the SEM-PLS method to a sample of 151 Gen Z respondents selected via purposive sampling. The results indicate that Ethics was found to have a strong and significant positive influence, confirming that intrinsic personal values are the primary driver of investment decisions. Conversely, Digital Banking and Social Media showed no significant influence, attributed to the minimal integration of ESG analysis features on digital platforms and Gen Z’s skepticism toward greenwashing. Furthermore, both AI and Financial Literacy failed to moderate the relationships, signalling a gap in technology implementation and a lack of specific ESG literacy.